Paulo Freire e a simula????o na forma????o m??dica - Duran, Cinthya Cosme Gutierrez (2014)
This thesis is a study of simulation as a pedagogical resource used in medical training. The development of technologies based in simulators has grown exponentially and has enabled the advancement of these resources aimed at training health professionals. Currently, the latest generation simulators reproduce with great accuracy the most diverse biological and pathological behaviors of the human body. These activities represent an innovation to the traditional medical education. However, it is noticed that little has been studied about the pedagogical process simulation, which practices are marked basically by reproduction techniques, also used in other areas and professional contexts. This thesis tried to demonstrate, by examination of the conceptions and practices of medical simulation, what kind of pedagogical conception it matches. This observation assessed whether the practices of simulation in medical education leading to the problem-based education or reproduce traditional forms of teaching, called banking perspectives. In this study, the structural axis of the research was to understand whether teachers and students visualize the simulation as an opportunity to contribute to a more dialogical education and hence emancipatory in their processes to meet, explain and intervene in the reality of the health conditions of population. For the guidance of the study, we have searched to some categories of analysis of Paulo Freire s thoughts, among them, " banking education " , " liberating education " , " dialogue" and "reading of the world". Besides the literature research, this thesis analyzes the results of a series of empirical data collected using the Likert survey and focal groups, with students and professors of medical school. This research has shown that for more intense that nowadays is the investment practices of simulation, still predominates in educational practice in the area of health, a conservative vision of education that Paulo Freire called banking education. On the other hand, in the speech of professors and students about simulation, we have realized there was evidence of construction of another problem-based education, in which the dialogue and reading of the world gain significant spaces in the process of knowledge construction. In conclusion, in this research, a simulation pedagogy, outlined from Paulo Freire s assumptions, allows to confirm that much more than a simple tool of technological innovation, simulation must be used as a pedagogical and methodological assumption of virtual reconstruction of reality, in which professors and students are at the same time, teaching and student staff in the pedagogical relationship, which purpose is to qualify the theory and practice to better intervene in the process of humanization of the world.